Short Sexual Well-Being Scale – a cross-sectional validation among transgender and cisgender people - Rafał Gerymski (Health Psychology Report, 2020)
Background Sexual well-being is often mistakenly operationalized simply as sexual satisfaction. The concept of sexual well-being has been often used as an umbrella term for positive aspects of sexuality, apart from its negative spheres. A new concept of sexual well-being was proposed in line with the World Health Organization (WHO) definition of sexual health. The definition tried to enrich the concept of sexual well-being, but it did not solve the problem of its operationalization. The aim of this study was to verify the psychometric properties of the new scale measuring the concept of sexual well-being.